THE IMPACT OF TRANSFORMATIONAL LEADERSHIP ON JOB SATISFACTION IN ALGERIAN WATERS COMPANIES - Slimani, Ilyes; Berbaoui, Kamel; Douli, Souad (International Journal For Research In Business, Management And Accounting, 2019)
The aim of this study is to reveals the The Impact of transformational leadership on Job Satisfaction in Algerian Waters Companies. The results also show that coaches were perceived by their employees as utilizing moderate transformational leadership behaviors. Intellectual stimulation was the most perceived leadership behavior followed by idealized influence, inspirational motivation, and individual consideration. Moreover, the findings reveal a significant positive correlation between transformational leadership behaviors and employees’ satisfaction. The regression model indicated that transformational leadership factors, inspirational motivation, intellectual stimulation, and idealized influence were significant predictors of employees ’ satisfaction. The three-variable prediction model accounted for 3.234 of the variance in employees’ satisfaction.